Evaluation of adenosine deaminase activity in serum of cattle and buffaloes in the diagnosis of bovine tuberculosis - Dhaliwal, Navdeep Kaur (Vet World, 2020)
BACKGROUND AND AIM: Bovine tuberculosis (bTB) is a chronic bacterial disease of cattle caused by Mycobacterium bovis. bTB causes severe economic losses resulting from livestock deaths, chronic disease, and trade restrictions. Determination of serum levels of adenosine deaminase (ADA), an enzyme produced by monocytes/macrophages and lymphocytes, has been used in the diagnosis of human TB. This study aimed to evaluate the role of ADA enzyme activity in the diagnosis of bTB. MATERIALS AND METHODS: In this study, a total of 100 animals (cattle and buffaloes) were screened for bTB by comparative intradermal tuberculin test (CITT) and interferon-γ (IFN-γ) test and in serum samples obtained from 100 screened animals, ADA seric activity was evaluated using ADA-MTB kit procured from Tulip Diagnostics. RESULTS: A total of 18 animals were positive TB reactors by CITT, 8 were positive by IFN-γ, and 4 animals were positive by both CITT and IFN-γ. The average ADA value of bTB-positive animals either by CITT, IFN-γ, or both CITT and IFN-γ was 12.55 U/L, 14.8 U/L, and 18.36 U/L, respectively, in CID negative, it was 10.57 U/L and in IFN-γ negative, it was 10.59 U/L. CONCLUSION: The average ADA value of bTB-positive animals positive either by CITT, IFN-γ, or both CITT and IFN-γ was more than the average ADA value in animals negative for bTB by either of the tests.